Apolipoprotein A-IV polymorphism and its effect on plasma lipid and apolipoprotein concentrations. - P de Knijff; M Rosseneu; U Beisiegel; W de Keersgieter; R R Frants; L M Havekes (Journal of Lipid Research, 1988)
Recently, we determined the apolipoprotein E (apoE) phenotype distribution in 2,000 randomly selected 35-year-old male individuals by slab gel isoelectric focusing of delipidated plasma samples, followed by immunoblotting using anti-apoE antiserum. These blots have been successfully re-used for immunovisualization of apoA-IV isoelectric focusing patterns. In a population sample of 1,393 individuals, four distinct apoA-IV isoforms were detected, encoded by the alleles A-IV*0, A-IV*1, A-IV*2, and A-IV*3 with gene frequencies of 0.002, 0.901, 0.079, and 0.018, respectively. The mean of plasma cholesterol, triglyceride, apoB and E levels did not differ significantly among the different apoA-IV phenotype groups. For these lipoprotein parameters, less than 0.1% of the total phenotypic variance could be accounted for by the APOA-IV gene locus. Our results did not show any effect of apoA-IV polymorphism on plasma apoA-I levels nor could we find any correlation between plasma levels of apoA-I and apoA-IV within the different apoA-IV phenotype groups. The plasma level of apoA-IV in subjects bearing the A-IV*3 allele is significantly lower than in subjects without the A-IV*3 allele (5 mg/dl versus 14 mg/dl). We therefore conclude that, in contrast to the apoE polymorphism, the polymorphism at the APOA-IV locus does not influence any of the levels of the lipoprotein parameters considered except apoA-IV.